Keratinocyte growth factor impairs human thymic recovery from lymphopenia - Coles, Alasdair J.; Azzopardi, Laura; Kousin-Ezewu, Onajite; Mullay, Harpreet Kaur; Thompson, Sara A.J.; Jarvis, Lorna; Davies, Jessica; Howlett, Sarah; Rainbow, Daniel; Babar, Judith; Sadler, Timothy J.; Brown, J. William L.; et al. (JCI insight, 2019)
The lymphocyte-depleting antibody alemtuzumab is a highly effective treatment of relapsing-remitting multiple sclerosis (RRMS); however 50% of patients develop novel autoimmunity post-treatment. Most at risk are individuals who reconstitute their T-cell pool by proliferating residual cells, rather than producing new T-cells in the thymus; raising the possibility that autoimmunity might be prevented by increasing thymopoiesis. Keratinocyte growth factor (palifermin) promotes thymopoiesis in non-human primates. Following a dose-tolerability sub-study, individuals with RRMS (duration ≤10 years; expanded disability status scale ≤5·0; with ≥2 relapses in the previous 2 years) were randomised to placebo or 180mcg/kg/day palifermin, given for 3 days immediately prior to and after each cycle of alemtuzumab, with repeat doses at M1 and M3. The interim primary endpoint was naïve CD4+ T-cell count at M6. Exploratory endpoints included: number of recent thymic-emigrants (RTEs) and signal-joint T-cell receptor excision circles (sjTRECs)/mL of blood. The trial primary endpoint was incidence of autoimmunity at M30. At M6, individuals receiving palifermin had fewer naïve CD4+T-cells (2.229x107/L vs. 7.733x107/L; p=0.007), RTEs (16% vs. 34%) and sjTRECs/mL (1100 vs. 3396), leading to protocol-defined termination of recruitment. No difference was observed in the rate of autoimmunity between the two groupsConclusion: In contrast to animal studies, palifermin reduced thymopoiesis in our patients. These results offer a note of caution to those using palifermin to promote thymopoiesis in other settings, particularly in the oncology/haematology setting where alemtuzumab is often used as part of the conditioning regime. ClinicalTrials.gov NCT01712945Funding: MRC and Moulton Charitable Foundation.